Online tutor management system using mobile application (EziTutor) - Muhammad Khairil Akmal, Mohd Khairuddin (2018)
With today's technological advances, smartphones have become a useful facility. Hence, many applications are developed to achieve that goal. Among them, the Online Tutor Management System (EziTutor) which aims to help students and Tutors meet and interact with each other to make tuition classes. This application was developed due to the problems faced by many people in Malaysia especially the parents of that have children in school that they had to pay an expensive price to send their children to a tuition center or an extra class. It is a burden to parents who want to see their children excel like other children. In addition, the problem arises is the quality of the teaching staff and materials is irrelevant. This is because the instructors are not aware of and follow the syllabus taught in schools. There are also those who teach only to find some money regardless of is the knowledge that the student understands or not. As a result, the sacrifice of parents of students seems to be futile and not beneficial to their children. Time and distance are also factoring why students have problems with tuition classes. This is because the class schedule has been set by the tuition and cannot be changed according to the suitability of the student. For students who are away from the tuition center, it is also a matter of commuting to the place. Another problem is that there is no other alternative ways for students to know who provides extra classes or tuition services outside their area except tuition centers. Because of these problems the EziTutor app is developed. This app can reduce the cost of the student to pay the tuition rate because there are no extra charges from the tuition center. This app can detect the location of the tutor who wants to make a tuition class that located near to the student. Students can compare the price of each tuition class and register the name in the class. Notifications will be given to tutor. With this application hopefully, it will help students to be excellent students especially for low-income families. The objective of this project is to develop mobile-based applications, and to improve the features of existing learning applications. Rapid Method of Application Development Cycle (RAD) has been selected as a software development software for this project.